Pelaksanaan Peradilan Adat Oleh Sarak Opat di Kabupaten Aceh Tengah - Bohari Muslim; Harry fauzi; Musmulyadi Musmulyadi (Pusat Riset dan Inovasi Nasional, 2025)
Central Aceh is one of the Regencies located in the center of the Province of Aceh which is dubbed as the Gayo plateau region, Aceh is a province in Indonesia that applies customary law in settling cases or disputes in the community through the Sarak Opat Kampung Customary Court, as regulated in The Aceh Qanun number 9 of 2008 concerning the Development of Customs and Customs was later reinforced by Governor Regulation Number 60 of 2013 concerning the Implementation of Customary and Customary Dispute / Dispute Settlement.This study aims to describe the function and authority and find out the procedures for implementing Customary Courts by Sarak Opat in Central Aceh District, then to find out the invoices that constrain Sarak Opat in carrying out customary justice and to find formulations that are obstacles in the implementation of adat justice in Aceh District The middle.This study uses empirical juridical research methods with research sites in Central Aceh District using secondary, primary and tertiary data, then the research data is collected through literature, interviews and observations. From the results of the data are further arranged descriptively analysis.